Plant genetic resources protection in the Mediterranean basin: the case of Sardinian forage species - Fois P.; Mura L.; Bullitta S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A regional bill on 'Protection of Sardinian local plant genetic resources and regulations regarding collection activities for scientific, economic and commercial purposes' has been worked out by the Authors of this paper and submitted to the Sardinian Regional Parliament in April 1999 by the first Author. Main objectives of the regional bill are the regulations and rationalization of collection activities of autochthonous plant genetic materials for economic and-or commercial purposes without constraints for the rights and interests of local populations and workers that take benefit from such resources. By means of this paper, we intend to bring the Sardinian Regional bill to knowledge of all people involved in local germplasm protection and of public opinion as a whole, its set of rules could in fact be useful at the Mediterranean level.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)